Comparative cytological and transcriptome analyses of ny2 mutant delayed degeneration of tapetal cells and promotes abnormal microspore development in neo-tetraploid rice - Kamara, Nabieu; Jiao, Yamin; Huang, Weicong; Cao, Lichong; Zhu, Lianjun; Zhao, Chongchong; Huang, Xu; Shivute, Fimanekeni Ndaitavela; Liu, Xiangdong; Wu, Jinwen; Shahid, Muhammad Qasim (Frontiers in Plant Science, 2023)
We aimed to investigate the genetic defects related to pollen development and infertility in NY2, a novel tetraploid rice germplasm known as neo-tetraploid rice. This rice variety was created through the crossbreeding and selective breeding of various autotetraploid rice lines and has previously shown high fertility. Our previous research has revealed that the NY2 gene, encoding a eukaryotic translation initiation factor 3 subunit E, regulates pollen fertility. However, the underlying mechanism behind this fertility is yet to be understood. To shed light on this matter, we performed a combined cytological and transcriptome analysis of the NY2 gene. Cytological analysis indicated that ny2 underwent abnormal tapetal cells, microspore, and middle layer development, which led to pollen abortion and ultimately to male sterility. Genetic analysis revealed that the F1 plants showed normal fertility and an obvious advantage for seed setting compared to ny2. Global gene expression analysis in ny2 revealed a total of 7545 genes were detected at the meiosis stage, and 3925 and 3620 displayed upregulation and downregulation, respectively. The genes were significantly enriched for the gene ontology (GO) term "carbohydrate metabolic process. Moreover, 9 genes related to tapetum or pollen fertility showed down-regulation, such as OsABCG26 (ATP Binding Cassette G26), TMS9-1 (Thermosensitive Male Sterility), EAT1 (Programmed cell death regulatory), KIN14M (Kinesin Motor), OsMT1a (Metallothionein), and OsSTRL2 (Atypical strictosidine synthase), which were validated by qRT-PCR. Further analyses of DEGs identified nine down-regulated transcription factor genes related to pollen development. NY2 is an important regulator of the development of tapetum and microspore. The regulatory gene network described in this study may offer important understandings into the molecular processes that underlie fertility control in tetraploid rice.